The Assessment of Modified Alvarado Score in the Diagnosis of Acute Appendicitis - A.K. Almujamaee , Baha Al deen (Diyala Journal of Medicine, 2019)
Background: Acute appendicitis is the most common surgical emergency. The case fatality rate has fallen to less than 0.1% for uncomplicated appendicitis as a result of early diagnosis and intervention. Objective: To evaluate the accuracy of the modified Alvarado score in the preoperative diagnosis of acute appendicitis and to compare the result of our study with others. Methods: A prospective study was carried on including seventy eight patients with presumptive diagnosis of acute appendicitis in Baquba general hospital for one year period ( first of jan. 2001 through 30 first of Dec. 2001 ) and the data were analyzed using a modified Alvarado score. Result: The presence of high score was found to be an easy stationary aid to early diagnosis of appendicitis. Conclusion: The modified Alvarado score is simple to use easy to apply. Effective particularly in men while diagnosis laparoscopy is advised in woman to minimize the false negative appendectomies. Still its validity has to be assessed in pediatric age group.